Children and the food price crisis - Dercon, S (2008)
The sharp increase in food prices both in world markets and in local markets since 2006 has raised serious concerns about the food and nutrition situation of poor families in many countries. Particularly in urban areas, where people cannot grow their own food, household budgets have been squeezed. The rapid price increases are especially bad news for young children, as any disruption to their nutrition tends to have serious long-term implications, both in terms of stunting, and lower educational outcomes, affecting their earning potential in later life. This policy brief looks at evidence from the Young Lives cohort study to show how the food price crisis will have both short-term and long-term impacts on children’s health, education, and psycho-social well-being. It also discusses policy options available to alleviate the consequences of the present crisis on children.